Meningkatkan Berpikir Kritis dan Pemahaman Siswa pada Pembelajaran Bahasa Inggris Menggunakan Media Film pada Siswa Kelas VIII SMPN 12 Tasikmalaya - Ghea Putri Melati (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research examines the problem of increasing the understanding and critical thinking abilities of students who use film media with students who use conventional learning methods. This research uses a quasi-experimental method with purposive sampling and the instruments used in this research are written tests and questionnaires. The population of this study was all students of class VIII SMPN 12 Tasikmalaya. The sample for this research was students in class VIII A. The instrument used in this research was a test of students' understanding and critical thinking abilities in the form of a questionnaire. Data analysis was carried out quantitatively. The results of the research show: 1) The increase in understanding of students who use film media is better than students who use conventional learning in English lessons in class. 2) The critical thinking of students who use film media is better than the critical thinking of students who use conventional learning in English lessons in class. Based on the research results, film media can improve students' understanding and critical thinking in English lessons. Film media can make modifications and adaptations according to the situation and conditions of the teaching and learning process.